Middle East policy
The most frequently cited journal on the Middle East region in the field of international affairs, Middle East Policy has been engaging thoughtful minds for more than 25 years. Since its inception in 1982, the journal has been recognized as a valuable addition to the Washington-based policy discussion. Middle East Policy provides an influential forum for a wide range of views on U.S. interests in the region and the value of the policies that are supposed to promote them.